Pseudocapacitive Conjugated Polyelectrolyte/2D Electrolyte Hydrogels with Enhanced Physico‐Electrochemical Properties. (5th January 2022) - Quek, Glenn; Su, Yude; Donato, Ricardo K.; Vázquez, Ricardo J.; Marangoni, Valeria S.; Ng, Pei Rou; Costa, Mariana C. F.; Kundukad, Binu; Novoselov, Konstantin S.; Neto, Antonio H. Castro; Bazan, Guillermo C.
Abstract: Conducting polymer hydrogels (CPHs) are an attractive class of materials that synergize the electrical properties of organic semiconductors with the physical properties of hydrogels. Of particular interest is the implementation of CPHs as electrode materials for electrochemical energy storage by taking advantage of redox‐tunable conjugated backbones and the large electroactive surface area. Herein, the use of 2D electrolytes as an effective post‐polymerization additive to enhance the pseudocapacitive performance of CPHs, is demonstrated. By using the self‐doped conjugated polyelectrolyte CPE‐K hydrogel as a model system, improvements in cycling stability, specific capacitance and working voltage window upon addition of the 2D electrolytes, are shown. Furthermore, positively charged 2D electrolytes to be more effective than their negatively charged counterparts are revealed. Rheology measurements and SEM imaging indicate that the 2D electrolytes serve as non‐covalent cross‐linkers that help in forming a mechanically more robust and highly percolated conducting network. These results provide a new and simple to execute post‐polymerization strategy to optimize the electrochemical performance of CPH‐based pseudocapacitors. Abstract : Conjugated polyelectrolyte (CPE) hydrogels are emerging electrode materials for pseudocapacitive energy storage. An effective method is reported to enhance the physico‐electrochemical properties of CPE hydrogels by introducing 2D electrolytes as cross‐linkers. The CPE/2D electrolyte composite shows significant improvements in cycling stability, specific capacitance, and working voltage window. This strategy provides guidance to designing CPE hydrogel‐based pseudocapacitors with improved electrochemical performances.